(untitled) (Computer systems and information technologies, 2023)
In the process of blowing, turbulent melt flows erode the ladle lining and its thickness de-creases due to mechanical erosion. The thickness of the steel ladle lining gradually becomes thinner with each casting. The degree of erosion depends on the tangential melt speed. In steel production, they try to slow down this wear, because each lining repair costs considerable time and resources. Scientists paid attention to this problem in publications, in particular, on mathematical modeling of lining wear. A large number of conditions of this process are subject to research, in particular, the number and location of blowing tuyeres, as well as blowing power. Firstly, it is necessary to quickly mix the impurity in the melt, and secondly, to preserve the lining of the ladle. Computer visualization and analysis of this process involves its course and results in the form of calculated fields, in particular, wear. The result fields are stored in a database. Also they are added and processed through a specially designed website. It allows researchers to register and fill in the experiment form, as well as add literature sources of data. The list of literature is used in almost all experiments to compare results. Simulation of the process at blowout rates of 40, 60 and 90 l/min and the number of blowout plugs (tuyeres) from one to three showed that the greatest scouring is predicted at the bottom, near the blowout plugs, and the transition to each higher blowout rate increases the scouring intensity by about 15%. Turning off the tuyeres after 1 minute of blowing significantly reduces erosion by at least 35%. If we consider the ladle wall, without disconnecting the tuyere, the flow rate of 90 l/min is the most destructive.